Penggunaan Keranjang Sampah Ergonomis Untuk Mengurangi Cidera Fisik Pemulung TPA Piyungan Bantul - Joko Susetyo; Titin Isna Oes; Monika Darmayanti (J.Abdimas: Community Health, 2021)
Scavengers play an important role in managing waste at the TPA because it helps reduce the amount of landfill piles so that it can extend the life of the landfill. The main tool used by scavengers to collect and transport trash is a basket made of bamboo slats. The basket uses a rope that is hung on one shoulder, and some are held above the head. The purpose of community service (PkM) is to produce ergonomic baskets that can reduce complaints of physical injuries to scavengers. This is done with anthropometric data, which is measuring the dimensions of the scavenger's body related to the use of baskets to get the appropriate basket size. The dimensions of the basket obtained are the length of the base = 38cm, the top of the basket = 50cm, the height of the basket = 51cm, and the length of the basket rope = 73cm. The implementation of the results of the redesign of the basket to the scavengers showed that complaints of stiffness/horror/stiffness/stiffness on the back and waist decreased by 100%, while complaints of stiffness/horror/stiffness/aches on the shoulders/shoulders decreased by 83.33%. The statistical difference test using Wilcoxon states that there is a very significant difference between before and after the design, P_value = 0.001.